Keuntungan, Batasan, dan Tantangan Penggunaan Building Information Modeling dalam Proses Pembelajaran - Muhammad Rafli Alrizqi; Ilham Fazri (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
This study investigates the use of Building Information Modeling (BIM) as a construction education technique on a campus setting. The planning, design, and project management processes are more accurate and efficient because to the growing use of BIM in the construction sector. However, there could be a number of problems and challenges when using BIM among students and teachers on a college campus. A literature analysis and questionnaires were employed in this study to gather information from students at one of Yogyakarta universities. The information covered students' understanding of BIM, their practical experience with it, and their perspectives on its advantages and disadvantages in the educational process. According to the study's findings, nearly all of college students are familiar with BIM. The survey also highlighted a number of obstacles that prevent the use of BIM on campuses, including a lack of infrastructure and resources, a curriculum that isn't properly integrated with BIM, and access issues for BIM software. The research also looked at the potential for creating OpenBIM as a way to improve teamwork and flexibility when using BIM on campuses. The adoption of BIM on campuses can have a substantial positive impact on students' readiness for a work market that is becoming more and more digitized and technologically focused.